Enhancing Physical Fitness and Health Awareness through a Preventive Health-Based Physical Education Model - Susanto, Ratno; Hermawati, Luluk; Rini Wulansa, Ekawati (BALE LITERASI, 2026)
This study aimed to develop and evaluate the effectiveness of a preventive health-based physical education intervention model in improving students’ physical fitness and health awareness. The study employed a research and development (R&D) approach combined with a quasi-experimental one-group pretest-posttest design. The development stages included needs analysis, model design, expert validation, limited trial, revision, field trial, pretest-posttest evaluation, and data analysis. A total of 30 students participated in the field trial. Data were collected using physical fitness tests, body mass index (BMI) measurements, healthy lifestyle behavior questionnaires, and observation sheets. The data were analyzed using descriptive and inferential statistics.The results showed that the intervention model was effective in improving students’ physical fitness and health-related behavior. Students’ average physical fitness score increased from 64.5 at pretest to 78.2 at posttest, with an improvement of 13.7 points. Improvements were also found in all major fitness components, including the 12-minute run test (32.4 to 38.6), push-up (21.3 to 28.7 repetitions/minute), sit-up (24.8 to 31.5 repetitions/minute), sit and reach (21.6 to 26.9 cm), and shuttle run performance, which improved from 12.8 to 11.3 seconds. BMI distribution also changed positively, with the proportion of students in the normal category increasing from 57% to 70%. In addition, healthy lifestyle behavior scores improved across all assessed aspects, including awareness of physical activity, regular exercise habits, preventive health knowledge, and healthy lifestyle behavior. Statistical analysis showed a significant difference between pretest and posttest results, supported by a moderate N-gain and high effect size.In conclusion, the preventive health-based physical education intervention model was effective in improving students’ physical fitness, BMI status, and health awareness.